2020
DOI: 10.3390/en13184854
|View full text |Cite
|
Sign up to set email alerts
|

A Theory for Power Extraction from Passive Accelerators and Confined Flows

Abstract: No valid fluid theory exists for power extraction from unpressurized confined flow. The absence of a valid model to determine baseline uniform power extraction in confined flows creates difficulties in characterizing the coefficient of power. Currently, the primary body of research has been limited to Diffuser Augmented Wind Turbines (DAWTs) and passive fluid accelerators. Fluid power is proportional to the cube of velocity; therefore, passive acceleration is a promising path to effective renewable energy. Hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Several experimental, theoretical, and numerical studies using the design of diffusers have demonstrated that it is possible to exceed the Betz limit. Freda et al [19] formulated a theory concerning power extraction from passive accelerators and confined flows. Their study highlights the significance of a system with a C p value greater than one, indicating that such a system can extract more energy than the kinetic energy in the stream tube of the maximum area of the accelerator projected forward.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental, theoretical, and numerical studies using the design of diffusers have demonstrated that it is possible to exceed the Betz limit. Freda et al [19] formulated a theory concerning power extraction from passive accelerators and confined flows. Their study highlights the significance of a system with a C p value greater than one, indicating that such a system can extract more energy than the kinetic energy in the stream tube of the maximum area of the accelerator projected forward.…”
Section: Introductionmentioning
confidence: 99%
“…The rotating part is held in place by a tall tower, which is used to fix it and deliver it to the required height. Magnets that pass through the static wire coil known as the solid component transform wind energy into electricity [4], [5]. The generation of alternating electricity occurs when a magnet moves through the stator.…”
Section: Introductionmentioning
confidence: 99%
“…While different AMs use different equation development methods, the averaging method is fundamental to all AMs, regardless of apparent differences in variables. 29 The possibility of reaching this limit using any duct or turbine is still undetermined. These studies demonstrate how PDs are used in ducted turbines for various applications.…”
Section: Introductionmentioning
confidence: 99%
“…There is no derivation, argument, or experimental evidence presented by the AMs to justify or validate this assumption. While different AMs use different equation development methods, the averaging method is fundamental to all AMs, regardless of apparent differences in variables 29 . The possibility of reaching this limit using any duct or turbine is still undetermined.…”
Section: Introductionmentioning
confidence: 99%